La editorial Minerva (1943-1946). Un ensayo de cultura popular y cristiana de las primeras mujeres del Opus Dei / The Minerva Publishing House (1943-1946). A venture in the field of popular Christian culture by the first women of Opus Dei - Mercedes Montero (Studia et Documenta)
This article deals with the activity of the Minerva publishing house between 1943 and 1946. This project was the initiative of several women of Opus Dei together with some other women who had no relation with the Work but who nevertheless wanted to be involved in the undertaking. The aim was to foster the reading of classical and modern books presented in an attractive way. Although only three publications were printed, it can be considered as the first of many apostolic initiatives in the field of public opinion, initiatives which were promoted afterwards by other members of Opus Dei together with people who shared similar ideals.